Urban landscape units and spatial grid networks of the land, water and mountain system using a multiple factor overlap approach: A lowland case study of Hangzhou City, China - J.R. Shi; Y.X. Lei; Z. Wang; K. Hokao; X.M. Zhao (Lowland Technology International, 2016)
The issue that many Chinese cities follow similar international styles degrades local cultural customs and regional ethnic features, and it is drawing much attention of citizens, governors and designers. Some research has corroborated the effectiveness of correlation and integrity of native urban sceneries, to deal with the above issue. Urban landscape can be regarded as a dynamic network system, comprising some interlinked spots and regions. Based on the current situation and academic proceedings, this research introduced the concept of urban landscape network. By a case study of Hangzhou City construction, this paper conducted a grid analysis of the landscape grid network, and built four sub-networks: natural scenery, historical development, road transportation, and land use. Using variance analysis, correlation analysis, multiple regression analysis, this paper examines the relationship between the four sub-networks, and finally achieved an appropriate regression equation of the landscape network in accordance with the subjective satisfaction evaluation concerning the landscape quality.